Inadvertent Reduction of Symphyseal Diastasis During Computed Tomography. Issue 9 (September 2016) - Gibson, Peter D.; Adams, Mark R.; Koury, Kenneth L.; Shaath, M. K.; Sirkin, Michael S.; Reilly, Mark C.
Abstract : Objective: To determine the quantifiable difference in pubic symphysis diastasis when comparing computed tomography (CT) and pelvic radiographs in individuals with anterior pelvic ring injuries. Design: Retrospective chart and radiographic review. Setting: Level 1 trauma center. Patients/Participants: Between 2002 and 2013, all individuals requiring internal fixation of the anterior pelvic ring were reviewed. Of the 163 patients, 72 met the inclusion criteria. Patients with a symphysis dislocation were included if the pelvic radiograph and CT were performed without a pelvic binder, and imaging was adequate for required measurements. Intervention: Symphyseal diastasis was measured on the initial pelvic radiograph, the CT scout, and axial views. Main Outcome Measurements: Comparison of measured symphyseal diastasis on CT and pelvic radiographs. Results: Seventy-two patients met the inclusion criteria. Ninety-seven percent (70/72) had a reduction of their symphysis diastasis in the CT with an average reduction of 6.6 mm (Range, −2.6 to 35.5 mm). The average diastasis on radiograph was 26.3 mm compared with 19.7 mm on CT scout ( P < 0.001). Fourteen patients (19.2%) had a reduction from greater than 25 mm to less than 25 mm—a traditional cutoff for operative intervention. Conclusions: The anteroposterior pelvis radiograph remains an important part of the workup for trauma patients. Reliance on CT alone may underestimate the true degree of pelvic displacement. Failure to obtain pelvic radiographs in the acute setting limits the information in which the medical team can base both immediate and definitive decisions about pelvic ring injuries. Level of Evidence: Diagnostic level III. See Instructions for Authors for a complete description of levels of evidence.